1991
DOI: 10.1073/pnas.88.24.11545
|View full text |Cite
|
Sign up to set email alerts
|

Genes for two calcium-dependent cell adhesion molecules have similar structures and are arranged in tandem in the chicken genome.

Abstract: Genomic sequences immediately upstream of the translational start site for the chicken liver cell adhesion molecule (L-CAM) gene contain a second closely related gene, which, because of its location, we have designated the K-CAM gene. Less than 700 base pairs separate the presumed poly(A) site in the K-CAM gene from the translation initiation site for L-CAM. The sizes of exons 4-15 of the K-CAM gene are almost identical to those in the L-CAM gene and the exon/intron junctions occur at exactly equivalent positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…1 A) and all of the other genes characterized thus far in this cluster are interrupted by two introns. This intron͞exon organization is typical of classic cadherin genes (7)(8)(9)(10)(11). By contrast, the six ectodomains of every member of the human protocadherin ␣, ␤, and ␥ proteins are encoded in a single, unusually large exon (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A) and all of the other genes characterized thus far in this cluster are interrupted by two introns. This intron͞exon organization is typical of classic cadherin genes (7)(8)(9)(10)(11). By contrast, the six ectodomains of every member of the human protocadherin ␣, ␤, and ␥ proteins are encoded in a single, unusually large exon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the genomic organization of a number of classic cadherin genes revealed that the DNA sequences encoding individual ectodomains are interrupted by two introns (7)(8)(9)(10)(11)). An example of this is provided by human Ksp-cadherin (CDH16) gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the molecular basis of differential expression of cadherins as well as the evolution of the cadherin family, it is essential to reveal the genomic structure and chromosomal localization of each cadherin gene. Recently, the organizations of the chicken L-CAM (15) and K-CAM and the mouse P-cadherin genes were determined and compared (8,16), and the results of this study demonstrated that the exon and intron patterns are highly conserved between these three genes, although their size is very distinct. Regarding chromosomal localization, the human E-cadherin gene has been mapped to chromosome 16 (17) and the human N-cadherin gene has been mapped to chromosome 18 (18).…”
mentioning
confidence: 99%
“…More than 15 members of this family have been identified; these include E-cadherin (uvomorulin) (2, 3), P-cadherin (4), N-cadherin (5,6), liver cell adhesion molecule (L-CAM) (7), and K-CAM (8). These members share a similar primary structure that is divided into the extracellular, transmembrane, and cytoplasmic domains.…”
mentioning
confidence: 99%